Walking towards justice democratization in rural life - Bell, Michael, 1957-; Hendricks, Fred T.; Bacal, Azril, 1941- (Research in rural sociology and development ;, 2003)
Democracy is back, at least as a topic of concern among rural sociologists. The Neoliberal cast of the recent pursuit of globalization in world politics has led to the development of a wide range of critiques united by the same question: what about democracy? From this perspective, the main issue with globalization is the globalization of what - the market or the policy, the citizen as consumer or the citizen as citizen. This volume brings together some of the recent work of rural sociologists on democracy, in an effort to bring into sharper focus this work's distinctive contributions to the understanding the question of what is and should be globalized, with particular emphasis on rural concerns and rural people. Half the world still lives in rural areas, and the entire world depends upon the success of rural areas in providing the means for human subsistence. The impact of globalization on rural democratization thus has implications for everyone. The volume has three sections. The first draws together a range of theoretical work on rural democratization. The second explores processes of rural democratization in the rich countries of the world. The third investigates the distinctive manifestations of rural democratization efforts in the poor countries.